1994
DOI: 10.1088/0268-1242/9/12/021
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the film properties and the preparation conditions for a-Si:H grown by homogeneous chemical vapour deposition

Abstract: A study is presented of a-Si:H films prepared by homogeneous chemical vapour deposition (HOMOCVO). a-Si:H is known as a material which is rather stable against degradation by light. The effect of deposition conditions on the parameters characterizing the structural and electronic properties of the films is studied, and two general cases of constant and variable gas-phase conditions were considered.The obtained data suggest that the optoelectronic properties of HOMOCVO a-Si:H are not strongly related to the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The i-cSi-o also shows the stop-band reflection and the second-band and third-band reflections, although the positions are blue-shifted from those of i-aSi-o, consistent with the difference of refractive index between amorphous Si (n % 4.0) and crystalline Si (n % 3.45). [24] Notably, the position of the third band corresponds to the energy of the full photonic band gap according to theoretical calculations, [14] and its existence implies that both i-aSi-o and i-cSi-o have retained the good structural order of the silica opal. The inset in the SEM image further supports the high structural quality of i-cSi-o.…”
mentioning
confidence: 95%
“…The i-cSi-o also shows the stop-band reflection and the second-band and third-band reflections, although the positions are blue-shifted from those of i-aSi-o, consistent with the difference of refractive index between amorphous Si (n % 4.0) and crystalline Si (n % 3.45). [24] Notably, the position of the third band corresponds to the energy of the full photonic band gap according to theoretical calculations, [14] and its existence implies that both i-aSi-o and i-cSi-o have retained the good structural order of the silica opal. The inset in the SEM image further supports the high structural quality of i-cSi-o.…”
mentioning
confidence: 95%
“…There are two mechanisms for the penetration of sodium into the growing a-Si : H film: thermal diffusion and field-induced diffusion. The diffusion coefficient of sodium in a-Si : H at a deposition temperature of 563 K is 1.36 X lo-" m2 s -' (Zhang and Haneman 1987). This value is high enough to make the contribution of the thermal component significant.…”
Section: Results and Disc~jssionmentioning
confidence: 94%
“…The increased room-temperature conductivity and the lower values of activation energy in a-Si : H deposited on soda-lime glass substrates indicate that these films are doped with sodium. It has been suggested that sodium penetrates into the a-Si : H film during its growth and acts as a donor (Zhang andHaneman 1987, Nesheva and. The decrease in electrical conductivity and increase in activation energy on increasing the micropore density suggest that the doping level depends upon the amount of micropores and becomes lower in films with a higher porosity.…”
Section: Results and Disc~jssionmentioning
confidence: 99%
See 2 more Smart Citations